Population dynamics of Cynoglossus senegalensis from the coastal waters of Greater Accra, Ghana - Samuel K. K. Amponsah; Berchie Asiedu; Pierre Failler; Nii Amarquaye Commey (Academia Biology)
Some life history aspects, including population parameters of Senegalese tongue sole (Cynoglossus senegalensis), in the coastal waters of Ghana, were studied between July 2018 and June 2019. The length data from a total of 528 specimens from the coastal waters of the Greater Accra region of Ghana was analysed for growth parameters, mortality parameters and biological reference points. The von Bertalanffy growth parameters were estimated at asymptotic length (L∞) = 57.2 cm TL, growth rate (K) = 0.40 per year, and growth performance index (Φ′) = 3.115. Mortality parameters were calculated as total mortality rate (Z) = 0.81 yr−1, the natural mortality rate (M) = 0.56 yr-1, and fishing mortality rate (F) 0.26 yr-1. The exploitation rate (E) of 0.31 was lower than both the optimum level and the exploitation rate at MSY (Emax = 0.64), indicating that C. senegalensis fishery in Ghana is underexploited. However, for sustainable management of the species, there is the need for continuous monitoring of fishing efforts and improve data collection.